Website-Based Clinic Queue Information System - Putra, Muhammad Angga; Rosalina, Ria (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
One of the computer-based information systems is a website. Along with the development of technology, the website has become a fast way for people to get information and is also easily accessible. Dissemination or delivery of information carried out on online information systems can be accessed by anyone and anywhere with the condition that they are connected to the internet network. The purpose of this research is that people no longer need to go back and forth just to take the clinic queue number. The development methodology used is the SDLC (System Develop Life Cycle) method with the waterfall process model until the testing stage. The programming language used is PHP and the database uses MySQL. The expected result is to make the registration process easier, from initially having to queue first to register, then now being able to register through the website without having to go back and forth to the clinic just to queue to register.